The socio-political and ideological-cultural elements of the Italian nation and the national minority question in Italy - Vidau, Zaira (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2011)
Law 482, Norms Concerning the Protection of Historical Linguistic Minorities, perhaps historically the most important law on national minorities in Italian history, was enacted in 1999. This article analyses the socio-political and ideological-cultural elements of the Italian nation that led to the increase in political attention to the national minority question in Italy that was required for such a law to have been accepted. The two endogenous socio-political elements are the definition of the Italian nation in the civicsense and its crisis, which was induced by the Northern League (Lega Nord), as well as its relationship with the ethnic elements of the Italian nationality, such as the Italian language and its dialects. There are two exogenous socio-political elements as well: the weakness of the Italian civic nation caused by the historic presence of socio-political divisions on the state territory; and the absence of the theme of nationality and ethnicity in the intellectual debate of the post-war democratic period. The conclusions seem to confirm that, thanks to the new debate about Italian nationality in the nineties, the theme of national minorities could become an element of the current political discourse in Italy.
Keywords: Italija; Italy; manjšine; narodne manjšine; narodnostno vprašanje; pravno varstvo; manjšinska zakonodaja